Revision of Prosyntexis from the Lower Cretaceous Crato Formation of Brazil (Hymenoptera: Sepulcidae: Trematothoracinae) - Jattiot, Romain; Krogmann, Lars; Nel, André (Zootaxa, 2011)
The fossil Prosyntexis species from the Lower Cretaceous Crato Formation of Brazil are revised. The examination of three new specimens of the sepulcid species Prosyntexis gouleti Sharkey, 1990 allows amending its species diagnosis by adding new morphological characters, especially from the wing venation and from the hitherto unknown antenna. A close comparison with Prosyntexis legitima Martins-Neto et al., 2007 demonstrates that this species is a junior synonym of P. gouleti (syn. nov.). The taxonomic position of the genus Prosyntexis within Sepulcidae: Trematothoracinae and of the enigmatic Prosyntexis montsecensis Rasnitsyn and Ansorge, 2000 are discussed on the basis of the new morphological data.